COLLECTION DEVELOPMENT STRATEGY DURING THE COVID-19 PANDEMIC IN LIBRARY - Vanindah, Jeihan; Rohani, Laila (Academic Solution Publisher, 2023)
This research discusses the collection development strategy at the Medan City Library and Archives Service during the Covid-19 pandemic, where the core of this problem is how library managers create strategies to optimize collection development activities that are hampered during the pandemic, as well as implementing policies to overcome prominent changes. at the Medan City Library and Archives Service during the Covid-19 Pandemic. The type of research used in this thesis is qualitative research with a descriptive approach, namely describing and describing the data and then analyzing the data obtained from the field so that the data and information obtained are explained without any engineering. The data collection technique for this research is through a process of observation, interviews and documentation. There were 4 informants in this research, consisting of the head of the library materials development and processing section, library staff, and staff in the field of library materials conservation. The results of the research show that the changes that occurred during the Covid-19 pandemic in the Medan City Library and Archives Service were reduced visitor hours, reduced government budgets for libraries, and collection development activities such as selection and procurement of library materials were hampered. This causes library managers to make strategies by reducing procurement, minimizing designated collection branches and making plans to focus on electronic collections.